Revealing the time course of laser‐evoked potential habituation by high temporal resolution analysis. (8th July 2021) - Kersebaum, Dilara; Fabig, Sophie‐Charlotte; Sendel, Manon; Muntean, Alexandra Cristina; Baron, Ralf; Hüllemann, Philipp
Abstract: Background and Objectives: Reduced laser‐evoked potential (LEP) habituation indicates abnormal central pain processing. But the paradigm (four stimulation blocks a 25 stimuli) is time consuming and potentially omits important information on the exact habituation time course. This study examined whether a high temporal resolution (HTR) analysis (dividing the four stimulation blocks into 12 analysis blocks) can answer the following questions: (a) After how many stimuli does LEP habituation occur? (b) Is there a difference in LEP habituation in younger versus older subjects? (c) Is HTR applicable on radiculopathy patients? Methods: EEG data of 129 subjects were included. Thirty‐four young healthy and 28 advanced‐aged healthy subjects were tested with LEPs on the hand dorsum. Thirty‐seven radiculopathy patients and 30 controls were tested with LEPs on the L3 dermatome. The EEG data of the hand dorsa have been analysed conventionally and with HTR analysis. The applicability of HTR has been tested on radiculopathy patients and respective controls. Results: HTR was well feasible in young healthy subjects and revealed a strong habituation effect during the first 25 stimuli (i.e. within the first 5 min). After approximately 48 stimuli, no further significant habituation was detectable. LEP amplitudes were higher in young subjects. HTR was unsuitable for elderly subjects and middle‐aged radiculopathy patients. Conclusions: In young healthy subjects, HTR allows a shortening of the test protocol while providing a detailed information on the time course of LEP habituation. A shorter protocol might be useful for the applicability of the LEP paradigm for clinical and experimental settings as well as pharmacological studies. Significance: The usage of high temporal resolution (HTR) analysis in young healthy subjects enables a short test protocol and provides the exact time course of laser‐evoked potential habituation. This can be useful for the examination of neurological conditions affecting younger patients and for pharmacological studies. HTR was inapplicable in advanced‐aged subjects and patients with radiculopathy.